Scan QR code or get instant email to install app

Skip to content
#
Simplify: \(9-3(2^2)\) =

### Related Information

Question:

`_________`

.
A
\(−3\)

explanation

The Rules Guiding Order of Operations require that we address exponents first, then multiplications, then subtractions.

Exponent first: \(2^2=4\)

\(9 − 3(2^2\)) = \(9− 3(4)\)

Multiply: \(3(4) = 12\)

\(= 9 − 12\)

Add the opposite.

\(= 9 + (−12)\)

Add: \(9 + (−12)\)

\(= −3\)

Take more free practice tests for other GED topics with our ged now!

Comments